Predicting attitudes to diversity : the relationship between personal characteristics and prejudice towards diversity - Hildingsson, Johan Karl Ingvar (2021)
The aim of the current study was to evaluate the extent to which certain values, traits, cognitive styles, and cultural dimensions can a predict diversity attitudes of individuals. A sample of 104 respondents from a broad range of 39 nationalities represented answered a 5–10 minutes survey testing respondents’ views using the shorter TIPI (ten item personality index) of the Big Five personality traits dimension, SSVS (Short Schwartz’s Value Survey), Gelfand’s tightness/looseness dimension, cognitive conformity style & Hofstede’s masculinity dimension in addition to the attitudes to diversity scale focusing on two scales of prejudice against females and foreign ethnics. The study established strong links of findings clearly pointing to a distinct connection between harboring fewer negative attitudes to diversity and openness to experiences, benevolence, universalism, self-direction, and self-transcendence, whereas higher levels of conformity, conservation, power, and tradition in addition to the male gender all were found of harboring more negative attitudes to diversity.